Модель паровой турбины К-1000-60/1500-2 для исследования процессов управления - Северин, Валерий Петрович; Никулина, Елена Николаевна; Шевцов, Александр Сергеевич (НТУ "ХПІ", 2017)
Приведены уравнения переходных режимов паровой турбины. Путем преобразования уравнений турбины построена нелинейная модель паровой турбины К-1000-60/1500-2 как объекта автоматического управления в относительных переменных состояния, учитывающая экспериментальные данные регулирующих органов и использующая минимальное количество вычислений. На основании этой модели для исследования режима сброса нагрузки построены графики изменения переменных давления и частоты.

Presentation of model of steam turbine К-1000-60/1500-2 in the state space of relative variables is the aim of the article. Using the physics laws equations describing the dynamics of NPP steam turbine as an automation object in variable modes are considered. By transforming the equations of the dynamics nonlinear model of the steam turbine in relative state variables is built as a system of differential equations in the Cauchy form. The model takes into account the experimental data of regulators and uses a minimal amount of computations. Graphs of nonlinear functions of flow coefficients of the variables of servomotors coordinate values of the control valve and control flap, derived from the experimental data, are constructed. Formulas for the calculation and the calculated values of the constants parameters of the model are given. The input variables of the model are the coordinates of the servomotors of control valve and control flaps, as well as the power of the electric generator. On the basis of the turbine model for the study of the load shedding mode of electric generator graphs of pressure variables in steam volumes and speed of the rotor are constructed by numerical integration of the differential equations system for given functions of closing of servomotors of control valve and control flap. The maximum casting speed of turbine rotor is 7.36 % of the nominal frequency value. Similarly, nonlinear model of a steam turbine K-1000-60/1500-2 can be obtained. Models nuclear steam turbines in relative variables with the minimum number of calculations can be used to optimize the control system parameters of the steam turbine of nuclear power plant.
Model of steam turbine K-1000-60/1500-2 for control processes research
Keywords: паровая турбина; объект управления; уравнения динамики; нелинейная модель; переходный режим; steam turbine; object of control; dynamic equations; nonlinear model; transition mode